ACCION DEL ALUMBRE SOBRE LAS SALMONELLA TYPHI Y S PARATYPHI A Y B SU APLICACION EN LA INMUNIZACION ACTIVA ARTIFICIAL CONTRA LAS FIEBRES TIFOIDEA Y PARATIFOIDEAS CON UNA SOLA DOSIS DE VACUNA PRECIPITADA POR ALUMBRE - LEON, ALBERTO P (Universidad S, Departamento Agricultura, CD MEXICO, DF, MEX, 1943)
Alum precipitates of Vi strains of Eberthella typhosa and Salmonella paratyphi B and of S paratyphi A previously sensitized with immune serum are sterile The bactericidal effect of the alum is independent of the precipitating action; alum preserves and
REV INST SALUBR ENFERM TROP
Keywords: ACCION, ALUMBRE, SALMONELLA, APLICACION, INMUNIZACION, ACTIVA, FIEBRES, TIFOIDEA, PARATIFOIDEAS, DOSIS, VACUNA, PRECIPITADA, ALUMBRE; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS